Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(x^2-2xy+y^2\right)+\left(y^2+2y+1\right)=\left(x-y\right)^2+\left(y+1\right)^2\)
b) \(\left(z^2-6z+9\right)+\left(t^2+4t+4\right)=\left(z-3\right)^2+\left(t+2\right)^2\)
c) \(\left(4x^2-4xz+z^2\right)+\left(z^2-2z+1\right)=\left(4x-z\right)^2+\left(z-1\right)^2\)
a) \(x^2+10x+26+y^2+2y\)
\(=\left(x^2+10x+25\right)+\left(y^2+2y+1\right)\)
\(\left(x+5\right)^2+\left(y+1\right)^2\)
b) \(x^2-2xy+2y^2+2y+1\)
\(=\left(x^2-2xy+y^2\right)+\left(y^2+2y+1\right)\)
\(=\left(x-y\right)^2+\left(y+1\right)^2\)
c) \(z^2-6z+13+t^2+4t\)
\(=\left(z^2-6x+9\right)+\left(t^2+4t+4\right)\)
\(=\left(z-3\right)^2+\left(t+2\right)^2\)
d) \(4x^2-2z^2-2xz-2z+1\)
\(=\left(4x^2-4xz+z^2\right)+\left(z^2-2z+1\right)\)
\(=\left(2x-z\right)^2+\left(z-1\right)^2\)
a) (a + b + c)2 + a2 + b2 + c2
= (a2 + b2 + c2 + 2ab + 2bc + 2ac) + a2 + b2 + c2
= (a2 + b2 + 2ab) + (a2 + c2 + 2ac) + (b2 + c2 + 2bc)
= (a + b)2 + (a + c)2 + (b + c)2
b) 2(a - b)(c - b) + 2(b - a)(c - a) + 2(b - c)(a - c)
= 2ac - 2ab - 2bc + 2b2 + 2bc - 2ab - 2ac + 2a2 + 2ab - 2bc - 2ac + 2c2
= 2b2 - 2ab + 2a2 - 2bc - 2ac + 2c2
= (a2 - 2ab + b2) + (b2 - 2bc + c2) + (c2 - 2ac + a2)
= (a - b)2 + (b - c)2 + (c - a)2
a) (a+b+c)2 +a2 +b2 +c2 = a2 +b2 +c2 +2ab+2bc +2ca + a2 +b2 +c2 = 2a2 +2b2 +2c2 +2ab+2bc+2ac
=(a2 +2ab+b2 ) +(c2 +2bc+b2) +(c2 +2ca +a2 ) =(a+b)2 +(b+c)2 +(c+a)2
a) \(9x^2-6x+1\)
\(=\left(3x\right)^2-2\cdot3\cdot x+1^2\)
\(=\left(3x-1\right)^2\)
b) \(\left(2x+3y\right)^2+2\left(2x+3y\right)+1\)
\(=\left(2x+3y+1\right)^2\)
1a/ z2 - 6z + 5 - t2 - 4t = z2 - 2 . 3z + 32 - 4 - t2 - 4t = (z2 - 2 . 3z + 32) - (22 + 2 . 2t + t2) = (z - 3)2 - (2 + t)2
b/ x2 - 2xy + 2y2 + 2y2 + 1 = x2 - 2xy + y2 + y2 + 2y + 1 = (x2 - 2xy + y2) + (y2 + 2y + 1) = (x - y)2 + (y + 1)2
c/ 4x2 - 12x - y2 + 2y + 8 = (2x)2 - 12x - y2 + 2y + 32 - 1 = [ (2x)2 - 2 . 3 . 2x + 32 ] - (y2 - 2y + 1) = (2x - 3)2 - (y - 1)2
2a/ (x + y + 4)(x + y - 4) = x2 + xy - 4x + xy + y2 - 4y + 4x + 4y + 16 = x2 + (xy + xy) + (-4x + 4x) + (-4y + 4y) + y2 + 16
= x2 + 2xy + y2 + 42 = (x + y)2 + 42
b/ (x - y + 6)(x + y - 6) = x2 + xy - 6x - xy - y2 + 6y + 6x + 6y - 36 = x2 + (xy - xy) + (-6x + 6x) + (6y + 6y) - y2 - 36
= x2 - y2 + 12y - 62 = x2 - (y2 - 12y + 62) = x2 - (y2 - 2 . 6y + 62) = x2 - (y - 6)2
c/ (y + 2z - 3)(y - 2z - 3) = y2 -2yz - 3y + 2yz - 4z2 - 6z - 3y + 6z + 9 = y2 + (-2yz + 2yz) + (-3y - 3y) + (-6z + 6z) - 4z2 + 9
= y2 - 6y - 4z2 + 9 = (y2 - 6y + 9) - 4z2 = (y - 3)2 - (2z)2
d/ (x + 2y + 3z)(2y + 3z - x) = 2xy + 3xz - x2 + 4y2 + 6yz - 2xy + 6yz + 9z2 - 3xz = (2xy - 2xy) + (3xz - 3xz) - x2 + (6yz + 6yz) + 9z2 + 4y2
= -x2 + 4y2 + 12yz + 9z2 = (4y2 + 12yz + 9z2) - x2 = [ (2y)2 + 2 . 2 . 3yz + (3z)2 ] - x2 = (2y + 3z)2 - x2
\(x^2+2y^2-2xy+2y+1\)
\(=x^2-2xy+y^2+y^2+2y+1\)
\(=\left(x-y\right)^2+\left(y+1\right)^2\)
a) \(x^2-6x+13+t^2+4t\Leftrightarrow\left(x^2-6x+9\right)+\left(t^2+4t+4\right)\)
\(\Leftrightarrow\left(x-3\right)^2+\left(t+2\right)^2\)
b) \(4x^2+2z^2-4xz-2z+1\Leftrightarrow\left(4x^2-4xz+z^2\right)+\left(z^2-2z+1\right)\)
\(\Leftrightarrow\left(2x-z\right)^2+\left(z-1\right)^2\)